THE DISTRIBUTION AND ABUNDANCE OF DECAPOD AND FISH COMMUNITIES IN CLEVELAND BAY, AUSTRALIA - Andhika Prima Prasetyo; Rudy Masuswo Purwoko (Research Center for Fisheries, 2016)
Spatial and temporal variations in the fish and decapod communities were investigated at three stations in Cleveland Bay along with other zooplankton and phytoplankton communities. The linkage between biological assemblages and physical properties of the ocean was explained to develop better understanding of population dynamic of planktonic communities. Biological and physical properties data were gathered in 3 stations by 6 different trips. The results show that there is a significant association between daytime and tidal period to the abundance of planktonic communities (P < 0.05). Spatial distribution of fish and decapod communities are likely explained by “predator pit” and “match/mismatch” concepts to increase the survival probability along with physical properties of the ocean.